2018
DOI: 10.1002/ijc.31289
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies using miR‐32‐5p to suppress clear cell renal cell carcinoma metastasis via altering the miR‐32‐5p/TR4/HGF/Met signaling

Abstract: While testicular nuclear receptor 4 (TR4) may promote prostate cancer (PCa) metastasis, its role in the clear cell renal cell carcinoma (ccRCC) remains unclear. Here we found a higher expression of TR4 in ccRCC tumors from patients with distant metastases than those from metastasis-free patients, suggesting TR4 may play positive roles in the ccRCC metastasis. Results from multiple in vitro ccRCC cell lines also confirmed TR4's positive roles in promoting ccRCC cell invasion/migration via altering the microRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…Targeting TR4/lncTASR/AXL signaling with small molecules including TR4-shRNA, tretinoin, or metformin all led to increase sunitinib sensitivity to better suppress the RCC progression To link the above findings to the future potential clinical application, we were interested to find if any small molecules can be used as possible therapeutic interventions to target this newly identified TR4/lncTASR/AXL signaling. Among several likely candidates, including TR4-siRNAs [25,26], miRNAs [22], TR4 potential antagonists/agonists including tretinoin (Hu et al unpublished data), and metformin [27] that can suppress the TR4 function, we found that adding TR4-shRNA (See Fig. 1f, g), metformin or tretinoin (up to 10 μM), could also result in increasing the sunitinib sensitivity to better suppress the RCC OSRC-2 cell growth (Fig.…”
Section: Human Clinical Data Support the Tr4/lnctasr/axl Axis In The mentioning
confidence: 82%
See 1 more Smart Citation
“…Targeting TR4/lncTASR/AXL signaling with small molecules including TR4-shRNA, tretinoin, or metformin all led to increase sunitinib sensitivity to better suppress the RCC progression To link the above findings to the future potential clinical application, we were interested to find if any small molecules can be used as possible therapeutic interventions to target this newly identified TR4/lncTASR/AXL signaling. Among several likely candidates, including TR4-siRNAs [25,26], miRNAs [22], TR4 potential antagonists/agonists including tretinoin (Hu et al unpublished data), and metformin [27] that can suppress the TR4 function, we found that adding TR4-shRNA (See Fig. 1f, g), metformin or tretinoin (up to 10 μM), could also result in increasing the sunitinib sensitivity to better suppress the RCC OSRC-2 cell growth (Fig.…”
Section: Human Clinical Data Support the Tr4/lnctasr/axl Axis In The mentioning
confidence: 82%
“…As recent studies indicated that TR4 could also impact RCC progression [21,22], we were interested to see if hypoxia may function via altering TR4 to influence the sunitinib sensitivity. The results revealed that hypoxia could significantly increase TR4 expression in both RCC OSRC-2 and SW839 cells (Fig.…”
Section: Hypoxia Treatment Can Increase Rcc Resistance To Sunitinib Vmentioning
confidence: 99%
“…The tumor promoting role of TR4 has been documented in various cancers [9][10][11][12][13], promoting scientists to identify TR4 inhibitor for better treatment of cancers. Therefore, it is of importance and interest to develop small molecules which can speci cally inhibit TR4 activity.…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor, activated TR4 is translocated to the nucleus where it binds its recognized DNA element and regulates a bundle of genes. Now increasing evidence suggest that TR4 may also contribute to cancer development [9][10][11][12][13]. For instance, TR4 played a tumor promoting role in RCC by promoting vasculogenic mimicry formation and tumor metastasis [9].…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulation of miRs is observed in the majority of types of cancer, including RCC (14). In previous studies, numerous miRs have been demonstrated to be involved in RCC, including miR-720 (15), miR-203 (16), miR-204-3p (17) and miR-32-5p (18). miR-222 is…”
Section: Introductionmentioning
confidence: 99%